2023
DOI: 10.1101/2023.08.21.23293658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-linear mendelian randomization: detection of biases using negative controls with a focus on BMI, Vitamin D and LDL cholesterol

Fergus W Hamilton,
David A Hughes,
Wes Spiller
et al.

Abstract: Mendelian randomisation (MR) is an established technique in epidemiological investigation, using the principle of random allocation of genetic variants at conception to generate predicted causal effects of an exposure on an outcome. Extensions to this technique include non-linear approaches, that allow for differential effects of the exposure on the outcome depending on the level of the exposure. One popular method is the residual approach, which allows for stratification of the exposure via the level of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
(128 reference statements)
4
14
0
Order By: Relevance
“…Associations with traits that are competing risk factors in strata of UK Biobank are displayed in Figure 1 . As previously observed in the literature for other exposures 26 , there are clear patterns in genetic associations with age and sex across strata. While there is no overall association of the genetic score with age or sex, there are associations in several of the strata.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Associations with traits that are competing risk factors in strata of UK Biobank are displayed in Figure 1 . As previously observed in the literature for other exposures 26 , there are clear patterns in genetic associations with age and sex across strata. While there is no overall association of the genetic score with age or sex, there are associations in several of the strata.…”
Section: Resultssupporting
confidence: 79%
“…Further, recruitment into UK Biobank is dependent on age, sex, and other factors, which leads to bias in Mendelian randomization estimates. While the effect of moderate selection on Mendelian randomization estimates is often slight 33 , the extent of selection bias may differ between strata, leading to differential bias across stratum-specific estimates 26 . It is likely that age and sex are the strongest predictors of study participants, and differential genetic associations with these traits were observed in UK Biobank.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, we prefer to use MR to exclude exposures that are clearly inconsistent with a causal effect in the tested cell type or tissue. Finally, our results reinforce the need to include both positive and negative controls in MR analysis and use visualisation approaches to assess model fit [28].…”
Section: Discussionsupporting
confidence: 71%
“…The non-linear association was also suggested in recent meta-analyses of observational studies 6,44 . Nonetheless, there is a concern that the residual method may violate the assumption of constant genetic effects on serum 25(OH)D within each stratum 48 . To address this, the doubly-ranked method was developed to provide less biased estimate even in facing the violation of the constant assumption 42 .…”
Section: Discussionmentioning
confidence: 99%
“…To address this, the doubly-ranked method was developed to provide less biased estimate even in facing the violation of the constant assumption 42 . However, a recent study suggested that both methods may have yielded biased estimates because the authors found non-null associations between genetic instrument for serum 25(OH)D and age or sex as negative control outcomes within the UK Biobank data, in which the expected results should be null 48 . Hence, the observed inverse association between serum 25(OH)D and SBP within the lowest stratum using both methods in our study might also be due to unknown biases.…”
Section: Discussionmentioning
confidence: 99%